WORKSHOP MEMBANGUN KOMPETENSI MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 JAKARTA DALAM MENGELOLA SALES ORDER DAN PURCHASE ORDER PERUSAHAAN - Anggoro, Hendi Tri; Pravitasari, Endyastuti (Jurnal Abdimas Bina Bangsa, 2024)
Independent Competency-Based Internship (MBKM) activities are an integral part of higher education programs that aim to improve students' practical skills through direct experience in the industrial world. This study aims to evaluate the implementation of MBKM student activities. PT Pangkal Multikarya as one of the largest authorized distributors of YKK AP has 33 years of experience in the field of aluminum installation. PT Pangkal Multikarya has handled more than hundreds of projects ranging from residential houses, housing, banks, hotels, office buildings, showrooms, and shop houses to high-rise buildings. PT Pangkal Multikarya's services include the installation of window walls, curtain walls, frameless glass, hanging glass, ACP, and flexible glass. The research method used is a case study with data collection through interviews, observation, and document analysis. The results show that MBKM activities at PT Pangkal Multikarya provide opportunities for students to develop technical and non-technical skills relevant to the world of work. Students are involved in various projects and activities that are not only in the internship placement division, but also include other divisions in PT Pangkal Multikarya. Thus, the results of this service provide valuable insights into the implementation of MBKM activities at PT Pangkal Multikarya and provide a basis for the development of a more effective internship program in the future